Pragmatisme Instrumental Dalam Sketsa Pendidikan Islam Di Indonesia - Hendro Widodo (Faculty of Education and Teacher Training, Institut Agama Islam Negeri Pekalongan, 2019)
This article aims to provide a theoretical and practical picture of sketches of Islamic education in Indonesia in an instrumental pragmatism paradigm. The style of Islamic education in Indonesia is implemented in a Pragmatic-Instrumental pattern, which is seen in the practical application of the learning process in formal educational institutions, both from the educational objectives to be achieved, the concept of the teacher and the method of learning. Pragmatism-style education has placed humans as the measure of everything. Education is not only intended to gain knowledge but also to gain expertise. This gives an equal portion of what will be achieved in the affairs of the world and the hereafter. The concept of the balance of the hereafter is relevant to national education goals that the purpose of national education is the development of the potential of students to become human beings who believe in and fear God Almighty, noble, healthy, knowledgeable, capable, creative, independent and become democratic citizens. and responsible. Therefore, education becomes an instrument to develop all aspects of human potential.